Tham khảo :
\(272+\left(146-x\right)=118\)
\(146-x=118-272\)
\(146-x=-154\)
\(x=146-\left(-154\right)\)
\(\Rightarrow x=300\)
\(504:\left(16-3x\right)=72\)
\(16-3x=504:72\)
\(16-3x=7\)
\(3x=16-7\)
\(3x=9\)
\(x=9:3\)
\(\Rightarrow x=3\)
1=> 146-x=-154
=>x=300
2> =>16-3x=7
=>3x=9
=>x=3
a, 272 + ( 146 - x ) = 118
146 - x = 118 - 272
146 - x = -154
x = 146 - ( -154 )
x = 300
Vậy....
b, 504 : ( 16 - 3x ) = 72
16 - 3x = 7
3x = 16 - 7
3x = 9
x = 3
Vậy.....
Bài làm
a) 272 + ( 146 - x ) = 118
146 - x = 118 - 272
146 - x = -154
x = 146 - ( - 154 )
x = 300
Vậy x = 300
b) 504 : ( 16 - 3x ) = 72
16 - 3x = 504 : 72
16 - 3x = 7
3x = 16 - 7
3x = 9
x = 3
Vậy x = 3
# Học tốt #